Elapsed Time (Seconds) Distance Travelled (Feet)
1 6.2
2 12.4
3 18.6
4 24.8
To form an equation, we first need to check whether the changing rate is a linear or non-linear.
A linear rate would give the same changing rate every one second traveled
Distance traveled between second 1 and second 2 = 12.4 - 6.2 = 6.2
Distance traveled between second 2 and second 3 = 18.6 - 12.4 = 6.2
Distance traveled between second 3 and second 2 = 24.8 - 18.6 = 6.2
Since the increase is the same every second, 6.2 feet, our equation would be the linear equation which is in the form y = mx + c
Where 'm' represents the gradient (changing rate) and c represents the distance traveled when the time is zero, which is also zero
n = 1 ⇒ d = 6.2
n = 0 ⇒ d = 6.2 - 6.2 = 0
We have m = 6.2 and c = 0
The equation is f = 6.2n
Answer: Option 3